2006
DOI: 10.1017/bjn20061928
|View full text |Cite
|
Sign up to set email alerts
|

Anthocyanin-rich purple potato flake extract has antioxidant capacity and improves antioxidant potential in rats

Abstract: Anthocyanins from various vegetables and fruits have antioxidant activities, however, the bioactivities of coloured potato anthocyanins are not well studied. We examined the antioxidant capacities of pigmented fractions from purple potato flakes in vitro, and the antioxidant potentials of purple potato flakes in vivo. 1,1-Diphenyl-2-picrylhydrazyl radical scavenging activity of the pigmented fraction from Hokkai no. 92 (H92) potato flakes was higher than that from Kitamurasaki (KM) potato flakes. Extracts equi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
63
1
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 98 publications
(74 citation statements)
references
References 49 publications
(67 reference statements)
6
63
1
4
Order By: Relevance
“…Thus, the order of the antioxidant activity was 0 % < 2 % < 50% = 100% concentrations of CPF. The antioxidant activities of anthocyanins are well documented (Wang et al, 1997;Tsuda et al, 2000), and the observed lipid oxidation reduction in cooked pork sausages could be attributed to its high concentration in CPF (Han et al, 2006). Similar to these findings, Han et al (2006) also reported the reduced hepatic lipid oxidation in rats fed CPF.…”
Section: Resultssupporting
confidence: 65%
See 2 more Smart Citations
“…Thus, the order of the antioxidant activity was 0 % < 2 % < 50% = 100% concentrations of CPF. The antioxidant activities of anthocyanins are well documented (Wang et al, 1997;Tsuda et al, 2000), and the observed lipid oxidation reduction in cooked pork sausages could be attributed to its high concentration in CPF (Han et al, 2006). Similar to these findings, Han et al (2006) also reported the reduced hepatic lipid oxidation in rats fed CPF.…”
Section: Resultssupporting
confidence: 65%
“…Therefore, the 0.2% PSPP, which imparted a similar antioxidant effect as with 0.1% BHT, contained 0.0048% anthocyanins. According to our previous study (Han et al, 2006), the anthocyanin concentration in CPF was 0.214 g/100 g CPF. Thus, to achieve the same antioxidant activity as with 0.2% PSPP, approximately 2.2% CPF was mixed with the pork sausage mixture.…”
Section: Methodsmentioning
confidence: 81%
See 1 more Smart Citation
“…These results suggest that potato consumption may enhance antioxidant defense and improve the lipid metabolism. Similarly in a study performed by Han et al (2006) on rats fed with anthocyanin-rich purple potato flake extracts, it was shown that these extracts have antioxidant capacity with regard to radical scavenging activity and inhibition of linoleic acid oxidation; moreover, they would enhance hepatic Mn-SOD, Cu/Zn-SOD and GSH-Px mRNA expression suggesting a reduced hepatic lipid peroxidation and an improved antioxidant potential in the rats.…”
Section: Carotenoids and Polyphenolsmentioning
confidence: 81%
“…Being known for their antioxidant, anti-inflammatory and antimicrobial properties [4,7,8], polyphenolic compounds are a large group of phytochemicals divided into the following classes; flavonoids, phenolic acids, tannins and stilbenes [27]. Research has shown that their consumption can decrease the risk of chronic diseases, such as heart disease, type 2 diabetes and cancer [7,28,29,30]. Thus, the presence of these compounds in bread products with purple potatoes paste addition could be useful for the consumers.…”
Section: Evaluation Of Tac and Tpc In Bread Products With Different Pmentioning
confidence: 99%